Sistem Pendukung Keputusan Prioritas Alokasi Program Pembinaan UMKM di DKI Jakarta Menggunakan Metode MOORA - Fathur Rozi; Izma Nurhanifah Fauzi; Angelina Hadriani (STMIK Al Muslim, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the main pillars of the economy in DKI Jakarta, yet the distribution of development programs often faces challenges in determining target-oriented regional priorities. This study aims to develop a Decision Support System (DSS) to determine the priority allocation of MSME development programs across six administrative regions in DKI Jakarta. The method employed is Multi-Objective Optimization on the basis of Ratio Analysis (MOORA), emphasizing regional productivity levels as the primary criterion. The criteria used include productivity rate (income per business unit ratio), the number of business units, and total regional income based on secondary data from the Satu Data Jakarta portal for the 2019-2023 period. The results indicate that the MOORA method provides objective recommendations, with South Jakarta Administrative City ranking first with the highest optimization value (Yi = 0.5648), followed by West Jakarta and Central Jakarta. This system offers a strategic contribution for the government in distributing development resources more efficiently based on actual economic performance in each region.